Flexible noncontact electrodes for comfortable monitoring of physiological signals. (30th April 2019) - Liu, Shuting; Zhu, Mingxing; Liu, Xueyu; Samuel, Oluwarotimi Williams; Wang, Xin; Huang, Zhen; Wu, Wanqing; Chen, Shixiong; Li, Guanglin
Summary: Physiological signals such as electrocardiography (ECG), electromyography (EMG), and electroencephalography (EEG) could objectively reflect the functioning status of the human body and the monitoring of these signals is useful for various applications including brain computer interface, neurological rehabilitation, and long‐term healthcare monitoring. Currently, wet electrodes are commonly used for the monitoring of physiological signals and it usually requires conductive gels to achieve high quality recordings, which may cause discomfort to the patient and increase risk of skin allergy. In this study, a noncontact electrode made of a multilayer flexible printed circuit without any rigid electronic components on either side was proposed. The flexible noncontact electrode was capable of measuring physiological signals without any direct skin contact or conductive gels and could be bent freely according to the local shape to achieve optimal capacitive coupling with the skin surface. The results showed that the proposed flexible noncontact electrode could obtain different physiological signals with good quality compared with traditional wet electrodes. The ECG signals could be reliably measured with different insulation materials between the skin and the electrode, with up to five layers of insulation materials. It was also found that flexible electrode could achieve higher signal‐to‐noise ratio and therefore had better performance than traditional hard printed circuit board electrode, when measuring EMG signal through the cloth and EEG signals over the hair. The proposed method of this study might provide a novel and comfortable way to measure physiological signals for neurological rehabilitation, wearable devices, and other healthcare applications.